The Cranial Nerves and Foramina: A Visual Recall Device - Patrick Sylvester; Lisa M.J. Lee; Douglas J. Gould (Association of American Medical Colleges, 2012)
Abstract As cranial nerve anatomy is a relatively complicated subject, commonly requiring visual aids in additional to cadaveric dissection, students often have a difficult time mastering the content. Furthermore, there is a paucity of ancillary resources with images and/or diagrams to help students learn the material with efficiency. To that end, we have developed a diagram- and image-based recall device, a resource for learning the anatomy of the cranial nerves and associated skull foramina. By simplifying cranial nerve anatomy using step-by-step diagrams of stick figures and circles, in which each subsequent diagram builds on the preceding, students and instructors can easily memorize the necessary content as well as comprehend the anatomical relationship of the important structures. This 27 slide, diagram- and image-based learning resource on cranial nerves and skull foramina was created for use by faculty members, students, and residents in the medicine and allied health fields as a concise, yet comprehensive review. Depending on the user and the purpose of its use, the resource should take approximately 30-60 minutes to go through. Users are encouraged to go through each slide in sequence to utilize the resource most effectively for a simplified overview or review of cranial nerve anatomy. Instructors are recommended to use the resource as formal or informal course content to provide a concise overview of cranial nerve anatomy. The resource is also an ideal ancillary learning and review tool that may be used outside of class at any time and any place. Finally, all original images and diagrams provided in the PDF file may be adapted for use in a variety of educational settings to increase discussion and instructional efficiency in order to foster a comprehensive review.